Odpowiedzi

2010-03-06T17:03:16+01:00
6x(1/16) = 3/8

a w drugim
16,8 wyjdzie
2010-03-06T17:07:01+01:00
6×(½)³×(-¾)×(-⅔)= 6 * 1/8 * (-3/4) * (-2/3) = 6/8 * (-3/4) * (-2/3) = 6/8 * (-1/3) * (-1/1)= (-2/8)* (-1/1)= 2/8= 1/4

-2⅓×(-1½)²×(3,2)= (-7/3) * 9/4) * 32/10= (-21/4) * 32/10= (-168/10) = (- 16 i 8/10) = ( -16 i 4/5)


licze na naj:))
2010-03-06T17:07:02+01:00
A)
6 × ( ½)³ × (-¾) × (-⅔) = 6 × 1/8 × (-3/4) × (-2/3) = 6/8 × 1/2 = 6/16 = 3/8

b)
-2⅓ × (-1½)² × (3,2)= (-3/2) × (-3/2)² × 32/10 = (-3/2) × 9/2 × 16/5 = (-27/4) × 16/5 = -432/20 = -21,6